Modeling in Educational Research; A path Analysis Model - BOUAICHA , Noura; BOUBLAL , Messaoud (Social Empowerment Journal, 2024)
This study aims to provide an analytical review of the use of the Path Analysis model in educational research. In recent years, there has been significant advancement in educational research methodologies, particularly with the development of statistical software. Among these methodologies is Structural Equation Modeling (SEM), which holds a prominent position in both educational and psychological research. SEM is considered part of advanced statistical analysis for data processing, relying on a range of statistical techniques such as multiple linear regression, path analysis, and confirmatory factor analysis (CFA). These methods allow for testing the validity of networks of relationships between variables in a holistic manner rather than in isolation. This paper will discuss the conditions for using the Path Analysis model, data processing methods, and interpretation of outcomes, through the analysis of various studies that have applied this approach to solve research problems.